The political economy of consulting firms in reform processes: the case of the World Health Organization - Julian Eckl; Tine Hanrieder (Review of International Political Economy, 2023)
Existing research interprets the rise of consulting firms in intergovernmental organizations (IGOs) primarily as evidence of the global spread of managerialism. We highlight that consultants are not merely carriers of business-like world cultural norms, but also part of contentious IGO politics and governance. We unpack the consulting black box and reconstruct how consulting firms are hired and active in IGOs. Analyzing the experiences of the World Health Organization (WHO), we show how IGOs have been informally `opened up' to consulting firms (and to their funders) and we investigate what the consequences of their privileged access are in practice. Consultants curate voices and input (including their own) into reform packages, promote certain contents, and engage in self-effacement practices that undermine accountability to stakeholders. The pivotal position of the consultants can have a disempowering effect on actors excluded from the consulting agreement or marginalized through consulting practices. We illustrate our general discussion by zooming in on the consultant-mediated reform of WHO's Roll Back Malaria partnership in 2015. Our analysis is based on primary documents, key informant interviews, informal conversations, and participant observation.
Keywords: 320; consulting firms; informal governance; private authority; Global governance; institutional reform; World Health Organization; Gates Foundation; McKinsey